Biological reasons for the phenomenon of eating disorders are more prevalent in the female population - Zhang, Vera (Transactions on Materials, Biotechnology and Life Sciences, 2023)
Eating disorders, characterized by irregular eating habits and distress concerning body image, have emerged as a significant global health challenge. With a specific focus on gender disparities, this paper explores the complex interplay of biological, environmental, and psychological factors contributing to the prevalence of eating disorders like anorexia nervosa, bulimia nervosa, and binge-eating disorder. The paper delves into evolutionary theories, arguing that historically ingrained reproductive strategies may predispose females to higher sensitivity toward body image, thus making them more susceptible to eating disorders. Additionally, the paper examines the strong correlation between affective disorders such as anxiety and depression, and the onset of eating disorders, drawing upon neurobiological mechanisms involving the hypothalamus and extended amygdala. We also investigate the role of dopamine and pleasure derived from eating, highlighting experimental findings that suggest females may experience more sustained pleasure from eating behaviors, potentially leading to higher susceptibility to eating disorders. The paper concludes by urging the need for gender-tailored therapeutic interventions and calls for a paradigm shift in societal attitudes to mitigate the risk and stigma associated with these disorders. Furthermore, it emphasizes the necessity for a multidisciplinary approach in both understanding and treating eating disorders, given their multifaceted etiology and impact on individual and public health.